Experimental characterization and numerical assessment of fatigue crack growth under thermo‐mechanical conditions. Issue 2 (18th February 2015) - Schlitzer, T.; Bauerbach, K.; Beier, H. T.; Fischaleck, M.; Langschwager, K.; Oechsner, M.; Rudolph, J.; Scholz, A.; Vormwald, M.; Willuweit, A.; Baumgartner, Jörg
<x xml:space="preserve">Abstract</x> The fatigue behavior of the austenitic stainless steel X6CrNiNb18‐10 (1.4550, AISI 347) is investigated. Experimental data are generated at room temperature, at elevated temperatures and further under thermo‐mechanical conditions. Research is focused on generating data for parameter identification, especially for the improvement of material models. The influence of temperature on the stress‐strain behavior and the fatigue life is presented. Finite element simulations are used to describe fatigue crack growth under thermo‐cyclic loading conditions. Using the example of a thick‐walled tube, the essential parameter for the crack growth rate, the effective cyclic J‐integral, is determined for eight temperature transients (defined by fluid temperature, heat transfer coefficient and inner pressure). An approximation of the effective cyclic J‐integral allows modeling without consideration of the crack geometry in the model.